Analysis of The Leadership Level of Students Participating in Volleyball and Non-Volleyball Extracurricular Activities - Agisna Nurhasanah; Carsiwan; Nuryadi (Journal of Physical Education Health and Sport, 2026)
Leadership is an important aspect in shaping student character, and can be developed not only through classroom learning but also through extracurricular activities. Volleyball, as a team sport, is thought to foster leadership skills such as teamwork, communication, and decision-making. However, there is no clear evidence as to whether involvement in these activities significantly differentiates the leadership levels of students compared to those who do not participate. Therefore, this study was conducted to examine differences in student leadership levels based on participation in volleyball extracurricular activities at Nyalindung 1 Middle School. This research uses a quantitative approach with a comparative descriptive design. The research sample consisted of 30 students consisting of 15 students who participated in volleyball extracurricular activities and 15 students who did not participate in volleyball extracurricular activities, using a purposive sampling technique. The research instrument used a student leadership questionnaire consisting of 30 statements with a 4-point Likert scale. The results of the reliability test showed a Cronbach's Alpha value of 0.862, which indicates a reliable instrument. The results of the descriptive analysis show that the average leadership score of students who participated in volleyball extracurricular activities was 108.07, while that of students who did not participate in volleyball extracurricular activities was 104.80. The results of the normality test showed that one of the data groups was not normally distributed, so the hypothesis test was carried out using the Mann-Whitney test. Hasil uji Mann-Whitney menunjukkan nilai Asymp. Sig. (2-tailed) sebesar 0,603 > 0,05, yang berarti tidak terdapat perbedaan yang signifikan antara kedua kelompok. The effect size value of 0.09 indicates that the difference that occurred was in the small effect category. Based on the research results, it can be concluded that students who participate in volleyball extracurricular activities have a slightly higher level of leadership descriptively, but the difference is not statistically significant.